1961
DOI: 10.1104/pp.36.5.663
|View full text |Cite
|
Sign up to set email alerts
|

Responses to gibberellin of light-requiring seeds of lettuce & Lepidium virginicum

Abstract: Many workers have shown that lettuce (7,9,12,13,14,15,17) and other photosensitive seeds (8,16,20,23) used in these studies. These seed bulks were stored dry in sealed jars at -12 C. These seeds were selected because the germination responses to light and temperature were known; Lepidium was the same species and Grand Rapids was the same sample as that used in the light studies reported previously (3,25,26).Seeds were planted in petri dishes on a double thickness of Whatman No. 2 filter paper wetted with 7.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

1961
1961
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
2
24
0
1
Order By: Relevance
“…When compared on cucumber seedlings, � was much more active than A3 in promoting hypo cotyl (74) and epicotyl growth (203), reversing the inhibition of stem growth by red light (74,112), and inhibiting root extension (74). When applied in total darkness, gibberellin A4 was 50 to 100 times more effective than AI, A2, and A3 in promoting the dark germination of Nicotiana tabacum L. (78) and lettuce (181), as well as the expansion of dark-grown Phaseolus and Raphanus leaf discs (78). Gibberellins Alp AfJ, and A6 were equally active on dwarf maize but As was relatively inactive (119).…”
Section: Relative Effectiveness Of the Gibberellinsmentioning
confidence: 98%
See 1 more Smart Citation
“…When compared on cucumber seedlings, � was much more active than A3 in promoting hypo cotyl (74) and epicotyl growth (203), reversing the inhibition of stem growth by red light (74,112), and inhibiting root extension (74). When applied in total darkness, gibberellin A4 was 50 to 100 times more effective than AI, A2, and A3 in promoting the dark germination of Nicotiana tabacum L. (78) and lettuce (181), as well as the expansion of dark-grown Phaseolus and Raphanus leaf discs (78). Gibberellins Alp AfJ, and A6 were equally active on dwarf maize but As was relatively inactive (119).…”
Section: Relative Effectiveness Of the Gibberellinsmentioning
confidence: 98%
“…The effects of several n-alkyl esters of gibberellin Aa on the germination of lettuce in dark ness were compared (160). Although the methyl, ethyl, n-propyl, n-butyl, n-amyl, and n-heptyl gibberellates increased the percentage of lettuce seed that germinated (160), dilute solutions of ethanol, used to dissolve the rela tively insoluble compounds in water, promoted germination (181). The observed activity may have resulted from the presence of ethanol and slow hydrolysis of the esters into the acid.…”
Section: Relative Effectiveness Of the Gibberellinsmentioning
confidence: 99%
“…In other systems, such as in the elongation of coleoptile segments (13), a major part of the CO2 action depends upon its ability to lower the pH of the medium. In seed germination (8,35), GA needed to be buffered at low pH to have a beneficial effect. In the present study, solutions of low pH did not stimulate germination or replace the requirement for CO2 (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report (27), we demonstrated that a combination of CM,4 with CO2 will completely overcome lettuce seed thermodormancy at 35 C under continuous light. This combination was effective, if it was added to seeds either at the start or after several days of imbibition.…”
mentioning
confidence: 99%
“…A aplicação exógena de reguladores de crescimento modifica, em algumas sementes, as exigências de temperatura e induz a germinação (Reynolds & Thompson 1973). Ácido abscísico (Figueiredo & Ferreira 1991), ácido giberélico, citocininas e etileno (Miller 1956, Toole & Carthy 1961, Usberti & Felippe 1979, Cardoso & Felippe 1983) estão relacionados, respectivamente, com inibição e promoção da germinação.…”
Section: Introductionunclassified